In vitro study of color stability of polycrystalline and monocrystalline ceramic brackets - Oliveira, Cibele Braga de [UNESP]; Maia, Luiz Guilherme Martins; Santos-pinto, Ary [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP] (Dental Press International, 2014)
OBJECTIVE:The aim of this in vitro study was to analyze color stability of monocrystalline and polycrystalline ceramic brackets after immersion in dye solutions.METHODS:Seven ceramic brackets of four commercial brands were tested: Two monocrystalline and two polycrystalline. The brackets were immersed in four dye solutions (coffee, red wine, Coke and black tea) and in artificial saliva for the following times: 24 hours, 7, 14 and 21 days, respectively. Color changes were measured by a spectrophotometer. Data were assessed by Multivariate Profile Analysis, Analysis of Variance (ANOVA) and Multiple Comparison Tests of means.RESULTS:There was a perceptible change of color in all ceramic brackets immersed in coffee (ΔE* Allure = 7.61, Inspire Ice = 6.09, Radiance = 6.69, Transcend = 7.44), black tea (ΔE* Allure = 6.24, Inspire Ice = 5.21, Radiance = 6.51, Transcend = 6.14) and red wine (ΔE* Allure = 6.49, Inspire Ice = 4.76, Radiance = 5.19, Transcend = 5.64), but no change was noticed in Coke and artificial saliva (ΔE < 3.7).CONCLUSION:Ceramic brackets undergo color change when exposed to solutions of coffee, black tea and red wine. However, the same crystalline structure, either monocrystalline or polycrystalline, do not follow the same or a similar pattern in color change, varying according to the bracket fabrication, which shows a lack of standardization in the manufacturing process. Coffee dye produced the most marked color changes after 21 days of immersion for most ceramic brackets evaluated.

OBJETIVO: esse estudo objetivou analisar, in vitro, a estabilidade de cor de braquetes cerâmicos monocristalinos e policristalinos após imersão em soluções corantes. MÉTODOS: sete braquetes cerâmicos de incisivo central superior direito, de quatro marcas comerciais, foram testados: dois monocristalinos e dois policristalinos. Os braquetes foram imersos em quatro soluções corantes (café, vinho tinto, Coca-Cola e chá preto) e em saliva artificial, separadamente, nos seguintes tempos: 24 horas, 7, 14 e 21 dias. As alterações de cor foram mensuradas por espectrofotômetro de refletância. Os dados foram avaliados pela Análise de Perfis Multivariados, Análise de Variância e teste de comparação múltipla de médias. RESULTADOS: houve alteração perceptível de cor em todos os braquetes cerâmicos após 21 dias de imersão nas soluções de café (ΔE* Allure = 7,61; Inspire Ice = 6,09; Radiance = 6,69; Transcend = 7,44), chá preto (ΔE* Allure = 6,24; Inspire Ice = 5,21; Radiance = 6,51; Transcend = 6,14) e vinho tinto (ΔE* Allure = 6,49; Inspire Ice = 4,76; Radiance = 5,19; Transcend = 5,64), porém, a alteração não foi perceptível para a Coca-Cola e saliva artificial (ΔE* < 3,7). CONCLUSÃO: braquetes cerâmicos sofrem alteração de cor quando em contato com café, chá preto e vinho tinto. No entanto, os braquetes de mesma constituição cristalina, sejam monocristalinos ou policristalinos, não seguem um padrão semelhante de alteração de cor, mas variam de acordo com o fabricante, o que mostra uma falta de padronização no processo de produção desses braquetes. O café foi a solução corante que mais produziu alteração de cor após 21 dias de imersão, para a maioria dos braquetes cerâmicos avaliados.
Keywords: Color; Ceramics; Orthodontic brackets; Cor; Cerâmica; Braquetes ortodônticos